Дайчин вангийн хүрээний түүхээс - Хатанбаатар, Н. (Historia Mongolarum, 2007)
Халхын томоохон хүрээ хийдийн нэг Дайчин вангийн хүрээний түүхийг хураангуйлан өгүүлжээ. 1666-1667 онд уг хүрээний суурийг Түшээт хан Чахундоржийн дүү Сэдшир баатар үндэслэсэн хэмээх таамаглал дэвшүүлсэн байна. 1937-1938 оны улс төрийн хэлмэгдүүлэлтийн үе уг хүрээ устаж үгүй болжээ. In this article the author tried to clear historical development of Daichin vang monastery, the one of the ancient monastery of Northern Mongolia from the 19th c beginning of the 20th c. Daichin van monastery founded by the activity of Baatar beil for spreading buddhism in our homeland. This monastery have passed through many stages of development during the historical process. There were over 3700 monks in the beginning of 2011 and these monks were divided into 6 aimaks and 5 datsans. The Daichin van monastery can be considered that its been one of the economic, religious and cultural center of Khаlkhа at beginning of the 20th century.